Analisis Kemampuan Literasi Matematika Peserta Didik pada Materi Program Linear dalam Pembelajaran Daring - Risa Utaminingsih; Subanji Subanji (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
Mathematical literacy skills indicate an individual's capacity to formulate, employ, and interpret and evaluate mathematics. Mathematical literacy skills are in line with numeracy skills which are an important component in solving problems in everyday life. The purpose of this study is to describe achievement of mathematics literacy skills in terms of aspects of the mathematical process in subject linear programming in online learning. This research is qualitative research with a descriptive approach. The data was collected by means of tests of mathematical literacy skills and interviews. The research subjects were 16 students of class XI MIPA 2 SMA Negeri 1 Gresik in the academic year 2020/2021. The results of this study in “Jajanan Tradisional” problem obtained an average score of formulate, employ, and interpret and evaluate are 89%, 68%, and 48%; whereas in “Gizi” Problem the average formulate’s score was 73%, employ’s score was 51%, and interpret and evaluate’s score was 21%. The achievement of students mathematical literacy test scores in “Jajanan Tradisional” problem was higher than students mathematical literacy test scores in “Gizi” Problem. Most of the students had not used diagrams, graphs and mathematical constructs, and took mathematical information from them. Most students only interpret mathematical results back to the real-world context without analyzing mathematical conclusions that make sense or not to the context of the problem, do not check the boundaries of mathematical concepts and mathematical solutions, and do not identify the limitations of the models used to solve problems.